Formulation of Novel Liquid Crystal (LC) Formulations with Skin-Permeation-Enhancing Abilities of Plantago lanceolata (PL) Extract and Their Assessment on HaCaT Cells - Dóra Kósa; Ágota Pető; Ferenc Fenyvesi; Judit Váradi; Miklós Vecsernyés; Sándor Gonda; Gábor Vasas; Pálma Fehér; Ildikó Bácskay; Zoltán Ujhelyi (Molecules, 2021)
Exposure to reactive oxygen species can easily result in serious diseases, such as hyperproliferative skin disorders or skin cancer. Herbal extracts are widely used as antioxidant sources in different compositions. The importance of antioxidant therapy in inflammatory conditions has increased. Innovative formulations can be used to improve the effects of these phytopharmacons. The bioactive compounds of Plantago lanceolata (PL) possess different effects, such as anti-inflammatory, antioxidant, and bactericidal pharmacological effects. The objective of this study was to formulate novel liquid crystal (LC) compositions to protect Plantago lanceolata extract from hydrolysis and to improve its effect. Since safety is an important aspect of pharmaceutical formulations, the biological properties of applied excipients and blends were evaluated using assorted in vitro methods on HaCaT cells. According to the antecedent toxicity screening evaluation, three surfactants were selected (Gelucire 44/14, Labrasol, and Lauroglycol 90) for the formulation. The dissolution rate of PL from the PL-LC systems was evaluated using a Franz diffusion chamber apparatus. The antioxidant properties of the PL-LC systems were evaluated with 2,2-diphenyl-1-picrylhydrazyl (DPPH) and malondialdehyde (MDA) assessments. Our results suggest that these compositions use a nontraditional, rapid-permeation pathway for the delivery of drugs, as the applied penetration enhancers reversibly alter the barrier properties of the outer stratum corneum. These excipients can be safe and highly tolerable thus, they could improve the patient’s experience and promote adherence.